HEAT EXCHANGE INTENSIFICATION IN SMALL CAPACITY GAS-TUBE HOT-WATER BOILER - Bodnar, Liliya; Stepanov, Dmytro; Boychuk, Roman (Scientific Works of Vinnytsia National Technical University, 2015)
Modern trends in development of small capacity boiling equipment are considered. New ways of heat exchange intensification in small-capacity hot-water boiler are investigated. The results of the experiments are analyzed. Methods of small capacity hot-water boilers heat calculation are substantiated. REFERENCES 1. Басок Б. И. Численное моделирование процессов аэродинамики в топке водогрейного котла со вторичным излучателем / Б. И. Басок., В. Г. Демченко, М. П. Мартыненко // Промышленная теплотехника. – 2006. – № 1. – С. 17 – 22. 2. Гришкова А. В. Уменьшение выбросов оксидов азота от водогрейных котлов путем внесения в топку промежуточного излучателя с оптимальными параметрами / А. В. Гришкова, Б. М. Красовский, А. Ю. Ракитин // Промышленная энергетика. – 2004. – № 5. – С. 32 – 33. 3. Петриков С. А. Прогрессивные способы интенсификации теплообмена в отопительных котлах / С. А. Петриков, Н. Н. Хованов // Промышленная энергетика. – 2003. – № 12. – С. 18 – 22. 4. Шахлина Н. А. Интенсификация теплообмена в газотрубных котлах с использованием профилированных поверхностей теплообмена : автореф. дис. на соискание ученой степени канд. техн. наук : спец. 05.14.04 “Промышленная теплоэнергетика” / Н. А. Шахлина. – Екатеринбург, 2007. – 20 с. 5. Колядин Е. А. Исследование и научное обоснование интенсификации теплообмена в судовых газотрубных утилизационных котлах : автореф. дис. на соискание ученой степени канд. техн. наук : спец. 05.08.05 “Судовые энергетические установки и их элементы ( главные и вспомогательные”/ Е. А. Колядин. – Астрахань, 2007. – 20 с. 6. Investigation of turbulators for fire tube boilers using exergy analysis [Електронний ресурс] / Betul Ayhan // Turkey Journal engineering environmental science. – 2001. – №5. – Р. 249 – 258. – Режим доступу до журн. : http://mistug.tubitak.gov.tr/bdyim/toc.php?dergi=muh&yilsayi=2001/4. 7. Neshumayev D. Experimental investigation of various turbulator inserts in gas-heated channels / D. Neshumayev, A. Laid, T. Tiikma // Experimental Thermal and Fluid Science. – 2004. – vol. 28(8). – Р. – 877 – 886. 8. Experimental and numerical investigation of combined heat transfer augmentation technique in gas-heated channels. In: Proceedings of the 4th International Conference on Heat Transfer, Fluid Mechanics and Thermodynamics, 18 – 23 Sept. [Електронний ресурс] / D. Neshumayev, T. Tiikma // Cairo, Egypt. – 2005. – Режим доступу: https://www.etis.ee/portaal/publicationInfo.aspx?PubVID=17&LanguageVID=2&FullTranslate=false. 9. Neshumayev D. Radiation Heat Transfer of Turbulator Inserts in Gas Heated Channels / D. Neshumayev, T. Tiikma, // Heat Transfer Research. – 2008. – vol. 39 (5). – P. 403 – 412. 10. Котли опалювальні водогрійні теплопродуктивністю до 100 кВт: Методи випробування і контролю теплотехнічних показників : ДСТУ 3948–2000. – [Чинний від 2001-01-01]. – К. : Держстандарт України, 2000. — 33 с. 11. Пат. 19637 Україна, МПК7 F 28 F 1/00. Вставка для теплообмінної труби / Ткаченко С. Й., Степанов Д. В., Боднар Л. А. заявник та патентовласник Вінницький нац. техн. університет. – № u200607988; – заявл. 17.07.06.; опубл.15.12.06.; Бюл. № 12. 12. Степанов Д. В. Експериментальні дослідження інтенсифікованого теплообміну в жаротрубному водогрійному котлі / Д. В. Степанов, С. Й. Ткаченко, Л. А. Боднар // Вісник Вінницького політехнічного інституту. – 2008. – № 2. – С. 44 – 47. 13. Тепловой расчет котлоагрегатов (нормативный метод). – СПб: НПО ЦКТИ, 1998. – 256 с. 14. Yrjola J. Modelling and experimental studies on heat transfer in the convection section of a biomass boiler / J. Yrjola., J. Paavilainen // Int. J. Energy Research. – 2006. – vol 30 (12) – P. 939 – 953. 15. Modelling and experimental study on wood chips boiler system with fuel drying and with different heat exchangers. Doctoral Dissertation [Електронний ресурс] / J. Yrjola // Helsinki University of Technology. Department of Mechanical Engineering. Laboratory of Applied Thermodynamics. Режим доступу до дисертації http://lib.tkk.fi/Diss/2006/isbn9512284391/isbn9512284391.pdf. 16. Neshumayev D., Tiikma T. Radiation heat transfer of turbulator inserts in gas heated channels / D. Neshumayev, T. Tiikma // Heat Transfer Research. – 2008. – vol. 39(5). – P. 403 – 412. 17. Исаченко В. П. Теплопередача / Исаченко В. П., Осипова В. А., Сукомел А. С. – Энергоиздат, 1981. – 412 с.